Genetic Deletion of KLHL1 Leads to Hyperexcitability in Hypothalamic POMC Neurons and Lack of Electrical Responses to Leptin - Perissinotti, Paula P.; Martínez-Hernández, Elizabeth; He, Yungui; Koob, Michael D.; Piedras-Rentería, Erika S. (Frontiers in Neuroscience, 2021)
Kelch-like 1 (KLHL1) is a neuronal actin-binding protein that modulates voltage-gated calcium channels. The KLHL1 KO model displays altered calcium channel expression in various brain regions. We analyzed the electrical behavior of hypothalamic POMC (proopiomelanocortin) neurons and their response to leptin. Leptin’s effects on POMC neurons include enhanced gene expression, activation of the ERK1/2 pathway and increased electrical excitability. The latter is initiated by activation of the Jak2-PI3K-PLC pathway, which activates TRPC1/5 (Transient Receptor Potential Cation) channels that in turn recruit T-type channel activity resulting in increased excitability. Here we report over-expression of CaV3.1 T-type channels in the hypothalamus of KLHL1 knockout (KO) mice increased T-type current density and enhanced POMC neuron basal excitability, rendering them electrically unresponsive to leptin. Electrical sensitivity to leptin was restored by partial blockade of T-type channels. The overexpression of hypothalamic T-type channels in POMC neurons may partially contribute to the obese and abnormal feeding phenotypes observed in KLHL1 KO mice.